Respostas

2014-07-25T19:19:47-03:00
a)x = 10
x+5=15
x=-5+15
x=10

b)x = -6
x=(-2)*(+3)
x=-6

c)x = 11
(-2)+x=+9
x = 2+9
x=11

d)x = 9
x*(-6)=+54
-6x = 54
6x = -54
x = 9

e)x = 5
2x+3=13
2x = 13-3
2x = 10
x = 5

f)x = 2
2x-1=3
2x = 3+1
2x = 4
x = 2

g)x = -1
3x+4=1
3x = 1 - 4
3x = -3
x = -1

Espero ter ajudado !
3 4 3
2014-07-25T19:21:22-03:00


a)x+5=15           x = 15 - 5        x =10
b)x=(-2)*(+3)     
x = - 6
c)(-2)+x=+9
       x = 9 + 2         x =11
d)x*(-6)=+54
      x = 54 / - 6      x = - 9
e)2x+3=13
         2x = 13 - 3      2x =10         x = 10/ 2      x = 5
f)2x-1=3
            2x = 3 + 1        2x = 4          x = 4/ 2        x = 2
g)3x+4=1
          3x = 1 - 4         3x = - 3        x = -3 / 3      x = -1







3 3 3